The Role Of Religion In Long-distance Marriage As Experienced By Malaysian Muslim Husbands - Melati Sumari; Mohd Izuddin Mashkor; Amira Najiha Yahya; Nurul Syuhaida Aman; Dini Farhana Baharudin (Sage Publishing, 2024)
Indexed by WOS/SCOPUS/ERA